Apically extruded debris and irrigants during root canal filling material removal using Reciproc Blue, WaveOne Gold, R-Endo and ProTaper Next systems - Cangul Keskin; Evren Sarıyılmaz (Tabriz University of Medical Sciences, 2018)
Background. The present study aimed to compare the amount of apically extruded debris and irrigants produced by various nickel-titanium instruments. Methods. A total of 100 single-rooted mandibular premolar teeth were root canal treated and prepared for agar gel model. The root canal fillings were removed using Reciproc Blue, ProTaper Next, R-Endo, WaveOne Gold systems or hand instrumentation. The mean weights of apically extruded materials were calculated. Data were statistically analyzed using one-way ANOVA and post hoc Bonferroni tests. Results. Hand instrumentation resulted in significantly more debris and irrigants than other systems (P<0.05). The mean amount of apically extruded debris and irrigants produced by Reciproc Blue system was significantly greater than motordriven instruments (P<0.05). No significant difference was detected between ProTaper Next and WaveOne Gold systems (P>0.05), while they both produced significantly less apically extruded material than R-Endo system (P<0.05). Conclusion. All the instruments caused apical extrusion. ProTaper Next and WaveOne Gold systems were associated with significantly less apical extrusion.